THE EFFECT OF POPULATION, HDI, AND GRDP ON THE LEVEL OF POVERTY IN THE KEDU RESIDENCY - Asyifa Lunawati; Hadi Sasana (Transpublika Publisher, 2022)
Poverty is a problem of non-accomplishment of individual welfare and is one of Indonesia's complex issues. Poverty is influenced by economic variables that are interrelated. This study was undertaken from 2012 to 2017 to examine the association between population, Human Development Index (HDI), and Gross Domestic Product (GDP) and poverty in the Kedu residence region. This study employs a regression method on panel data. Results indicated that population, HDI, and economic growth had a significant impact on the level of poverty in Kedu Residency. Meanwhile, the results of the F test indicate that the Population (JP), Human Development Index (HDI), and Economic Growth (GDP) variables have a significant impact on the Poverty Level simultaneously.